PEMBERDAYAAN GURU MATEMATIKA SMA BOJONEGORO MELALUI PELATIHAN AI DAN LATEX DALAM PENYUSUNAN SOAL TES KEMAMPUAN AKADEMIK - Fathoni, M Ivan Ariful; Al Farisy, Husen; Ardianti, Aprillia Dwi; Fitri, Anisa (As-Sidanah, 2025)
Mathematics test preparation by teachers is often conducted manually, resulting in inefficiency and inconsistent question quality. This community service program aimed to empower Mathematics MGMP teachers in Bojonegoro through training on the use of Artificial Intelligence (ChatGPT) and LaTeX in developing Academic Ability Test (AAT) items. The program was implemented through socialization, hands-on practice, dissemination, and evaluation using the Participatory Learning and Action (PLA/PAR) approach. The novelty of this activity lies in integrating ChatGPT, an AI-based question generator, with LaTeX, a professional formatting tool, both embedded within a participatory teacher-training model. The implementation significantly improved teachers’ competence in creating varied, structured, and well-formatted test items while strengthening collaborative work within MGMP. Moreover, teachers demonstrated increased efficiency and confidence in applying AI-based tools for mathematics assessment design. The program proved effective and replicable as a sustainable model for advancing digital competence and innovative assessment practices among mathematics educators.